AB0909 Effects of Combined Therapy with Prednisone and Methotrexate on B Cell Subpopulations in Patients with IGG4-Related Disease. (15th July 2016) - Lanzillotta, M.; Milani, R.; Campochiaro, C.; Bozzalla, E.; Berti, A.; Sabbadini, M.G.; Della Torre, E.
Abstract : Background: IgG4-Related Disease (IgG4-RD) is a systemic fibro-inflammatory condition characterized by oligoclonal expansion of IgG4+ class-switched plasmablasts (PBs) (1). PBs swiftly decline together with clinical improvement after rituximab, suggesting a role for B cells in the pathogenesis of IgG4-RD (2). Studies with alternative effective non B-cell depleting therapies (3) are needed in order to confirm the pathogenic importance of PBs and their utility as disease biomarkers. Objectives: To assess the impact of combined therapy with prednisone (PDN) and methotrexate (MTX) on B cell subpopulations in patients with IgG4-RD. Methods: Five patients with active biopsy proven IgG4-RD were treated with PDN (0.6–1 mg/kg) and MTX (10–20 mg per week). PDN was gradually tapered and withdrawn in 6 months. Disease activity, partial (PR) and complete response (CR) were assessed through the IgG4-RD Responder Index (IgG4-RD RI) (4). Serological, immunological and radiological studies were performed according to the clinical presentation. Flow cytometry was used to measure PBs (CD19+CD20-CD27+CD38+bright cells), naïve (CD19+CD20+CD27-CD38+ cells), and memory (CD19+CD20+CD27+CD38- cells) B cells at baseline, after 3 and 6 months of therapy. Nine age and sex matched subjects were used as healthy controls (HC). Results: At disease onset, the median IgG4-RD RI was 9 (normal <3). The median serum IgG4 level was 534 mg/dl (normal <135mg/dL). Circulating PBs were increased (median 7000 cells/mL) compared to HC (median 605 cells/mL; p<0.004). PBs showed a positive correlation with the number of organs involved (r=0.77), with serum IgG4 level (r=0.87), and with disease activity (r=0.73). The number of circulating memory B cells was comparable between IgG4-RD patients and HC (p=0.57). Naïve B cells were significantly lower in IgG4-RD patients compared to HC (p<0.05). After 6 months of therapy 4 patients achieved CR (IgG4-RD RI <3) and 1 PR. Serum IgG4 level decreased in all patients but normalized only in one patient at 6 months. Circulating PBs declined to levels comparable to HC (median 230 cells/mL, p=0.3). Memory B cells were unaffected by the therapy, while naïve B cells showed a declining trend, yet not statistically significant compared to baseline levels (p>0.05) Conclusions: PBs and naïve B cells are expanded and reduced, respectively, in patients with active IgG4-RD compared to HC. Combined therapy with PDN and MTX leads to clinical improvement and to normalization of circulating PBs. Naïve B cells slightly decrease, while memory B cells are not affected by immunosuppressive treatment References: Carruthers MN, et al. Rituximab for IgG4-related disease: a prospective, open-label trial. Ann Rheum Dis. 2015 Jun;74(6):1171–7. Wallace ZS, et al. Plasmablasts as a biomarker for IgG4-related disease, independent of serum IgG4 concentrations. Ann Rheum Dis. 2015 Jan;74(1):190–5. Della-Torre E, et al. Methotrexate for maintenance of remission in IgG4-related disease. Rheumatology (Oxford). 2015 Oct;54(10):1934–6. Carruthers MN, et al. Development of an IgG4-RD Responder Index. Int J Rheumatol. 2012;2012:259408. Disclosure of Interest: None declared